يوجياكارتا (MAN I) المدرسة المتفوقة: دراسة حالة عن مميزات المدرسة الثانوية الدينية الأولى - Jejen Musfah (Jurnal Pendidikan Islam, 2014)
This study departed from a reality that in the middle to low quality and learning achievement of madrasas, Madrasah Aliyah I (MAN I) Yogyakarta is a madrassa that can compete with the top schools in general. This study aims to analyze the various advantages of the Madrasah Aliyah I (MAN I) Yogyakarta. The method used in this research is descriptive method with qualitative approach. Data collection techniques are personal interviews, observation, and various documents related to the study material. Based on the research results, we concluded that the school has many advantages over other schools, among them cultivate a good personality, excel in science, and excel in the field of life skills. This school was considered a success in realizing its vision primarily because it is supported by the commitment of the principal, the competence of the teachers and administrative staff. In addition, a lack of compatibility between the vision and mission of the school curricula, completeness educational facilities and learning activities.